Implementasi PBL untuk Meningkatkan Hasil Belajar Mata Pelajaran IPA Materi Perubahan Energi pada Siswa Kelas IV - Dewi Fortuna; Lusy Tunik Muharlisiani; Mei Puspita Dewi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Science learning in elementary schools often faces challenges in improving students' learning outcomes, especially in the topic of energy transformation. This study aims to improve the learning outcomes of fourth-grade students in science, particularly in the topic of energy transformation, through the implementation of the Problem-Based Learning (PBL) model. This research uses the Classroom Action Research (CAR) method which consists of two cycles, each lasting one meeting. The results of the observation show that in the first cycle, students were active in learning but there were still some students who needed further guidance. In the second cycle, learning ran more effectively with students who were more focused and there were no longer any problems when divided into groups. The PBL model with the support of Canva presentation media successfully increased students' academic achievement, indicating that the PBL model is effective in helping students learn. The results of this study indicate that the PBL model can improve students' understanding and achievement in the topic of energy transformation. Therefore, the problem-based learning (PBL) model with the support of Canva presentation media is one of the effective approaches to improve the understanding of fourth-grade students in the topic of energy transformation.